An epigenome-wide association study based on cell type- specific whole-genome bisulfite sequencing: Screening for DNA methylation signatures associated with bone mass. Issue 5 (2017) - Komaki, Shohei; Ohmomo, Hideki; Hachiya, Tsuyoshi; Furukawa, Ryohei; Shiwa, Yuh; Satoh, Mamoru; Endo, Ryujin; Doita, Minoru; Sasaki, Makoto; Shimizu, Atsushi
No abstract available